Golgi Fragmentation in Human Patients with Chronic Atrial Fibrillation: A New Aspect of Remodeling - Jungk, Luisa; Franke, Heike; Salameh, Aida; Dhein, Stefan (The Thoracic and Cardiovascular Surgeon, 2019)
Background Atrial fibrillation (AF) is the most common chronic arrhythmia in elderly people and is accompanied by remodeling processes. While much is known about changes in ionic channels and in extracellular matrix, less is known about possible changes of intracellular structures.Objective We wanted to investigate, whether AF may also affect the structure of the Golgi apparatus and the microtubular network.Methods One-hundred fifty-three cardiac surgery patients were investigated [n = 24 in sinus rhythm (SR) and n = 129 with chronic AF of >1 year duration]. Tissue samples of the left atrial free wall were examined immunohistochemically. Golgi apparatus was detected by GM130 and its phosphorylated isoform. Furthermore, we investigated the length of the microtubules by α-tubulin staining. We also measured stathmin (phospho-S37), which is known to induce microtubule depolymerization. In addition, we investigated the cyclin-dependent kinase cdk5-activation, a typical stimulus for Golgi fragmentation, by measuring membrane-associated cdk5.Results We found significant fragmentation of the Golgi apparatus in AF together with a reduced fragment size. Significant more fragments of the Golgi were found lateral to the nucleus in AF, while the Golgi in SR was located more to the polar side of the nucleus, that is, in the longitudinal axis of the cell. This was accompanied by a significant reduction of the number of tubulin strands longer than 10 µm. These changes did not go along with an activation of stathmin, but with an increase in membrane association of cdk5.Conclusions The present data may show that AF associated remodeling also involves intracellular remodeling of the Golgi-microtubular apparatus.
Keywords: atrial fibrillation; human; Golgi apparatus; remodeling